The event and its publics - Babo, Isabel (2013)
From the intricate relationship between production and reception, I analyze the constitution of the media publics and others, by posing the question of how the arising of public events and corresponding news are not simply directed to the publics but also create them. To this end,I propose a reflection on the notion of public(s) and on the treatment of this notion by different authors. It is considered that publics are diverse and can organize themselves around objects, events, situations, actions, or around various experiences (a literary work, a newspaper report, the experience of a significant event, a catastrophe, a collective problem, a public cause, or an inquiry process). To lead this reflection, I discuss a hermeneutics of the publics to look at their activities in terms of their modalities and reception, interpretation and appropriation devices. I follow John Dewey’s pragmatic orientation, who, in The Public and its Problems (1927), sustains that a group of people only becomes a public if certain conditions occur: that the public “becomes aware of itself” and identifies the specific circumstances at the basis of its origin